Pengaruh Senam Nifas terhadap Pemulihan Fisik pada Ibu Nifas di Klinik BPM “S” Kabupaten Seluma - Widyaningsih, Sari; Selvianti, Dita; Hartati, Yosi (Universitas Malahayati, 2025)
ABSTRACT Postpartum care is needed to reduce the incidence of problems in postpartum mothers. Other factors that influence the physical recovery of post-partum mothers are the surrounding environment and family support, knowledge related to post-partum, adequate socio-economic security, personal hygiene, postpartum exercise and balanced nutritional intake. This research was conducted to determine the effect of postpartum exercise on the physical recovery of postpartum mothers at the BPM